Low-Level Corruption Tolerance: an "Action-Based" Approach for Peru and Latin America - Pozsgai Alvarez, Joseph (2015)
Since the beginning of the past decade, the tolerance of corruption by citizens of most Latin American countries has become a concept in its own right within the broader study of corruption. This construct, however, lacks a systematic approach and is yet to account for specific types of corruption tolerance or identify appropriate indicators to measure them. The present study addresses these voids by analyzing data provided by LAPOP's AmericasBarometer 2006 for Peru (a typical case for the incidence of bribery in Latin America) and the Global Corruption Barometer against a carefully constructed framework for the understanding of the phenomenon of corruption tolerance. The results indicate that attitudes toward specific types of low-level corruption should not be equated to citizens' decisions to engage in such behavior. They further suggest that the study of corruption tolerance has the potential to greatly improve our understanding of the determinants of corruption in developing c